STUDI TENTANG KEPUASAN KONSUMEN YANG DIPENGARUHI OLEH KUALITAS PRODUK DAN HARGA - Putra, Arif Rachman; Darmawan, Didit; Arifin, Samsul; Mardikaningsih, Rahayu; Sinambela, Ella Anastasya; Retnowati, Eli; Lestari, Utami Puji (JURNAL BISNIS KOLEGA, 2022)
The development of the times has brought society to a more modern direction, including in terms of beauty care. Therefore, it is not surprising to meet the community's need for this, more and more skincare clinics are found competing with each other to satisfy their consumers. With this phenomenon, this study was conducted to find out and prove that consumer satisfaction is caused by product quality and skincare prices. The explanatory research method was chosen for this study. The sample was obtained by accidental sampling technique so that there were 80 respondents. These 80 respondents met the criteria because they had visited and used products from one of the skincare clinics in Mojokerto City. This survey was conducted to observe and find out the opinions of consumers about their satisfaction based on product quality and price. This study requires primary data from 80 respondents, therefore the questions/statements in the questionnaire will be compiled. After data from 80 respondents have been collected and all meet the requirements, data tabulation, classical assumption test, multiple linear regression analysis, hypothesis testing and coefficient of determination test will be carried out using SPSS 26 for windows. It is known that the results of his research prove that product quality can have an effect on consumer satisfaction with significant results. Furthermore, for the price is also the same, can affect customer satisfaction significantly. It was also found that both (product quality and price) can affect consumer satisfaction with significant results.